Factor influencing consumers continuity making purchasing decision buy pirated product / Mohd Azlan Bakhari - Bakhari, Mohd Azlan (Faculty of Business and Management, 2013)
This study is aim the study on to study the factor influencing consumers continuity making purchasing decision buy pirated product. This study examines the relationship between four factors that could influence consumers continuity making purchasing decision buy pirated product are the social influence, pricing, product and personal traits. This study also tries to find out the most factors that influencing consumers continuity making purchasing decision buy pirated product. Data collected analyzed using Statistical Package for the Social Science (SPSS) for Windows. The sample population is 100 respondents which consisting of the consumers in Malaysia. All the respondents will be responding from the questionnaire that will provide to get the result on the factors influencing consumers continuity making purchasing decision buy pirated product. The result will be seen after all the frequency and correlation analysis will be using to test the study. Meanwhile all the four major of independent variable will be explained in the literature review and theoretical framework.